Hubungan Antara Intensitas Penggunaan Gadget Dengan Perkembangan Sosial Anak Usia Dini Di Korong Sicincin, Kecamatan 2x11 Enam Lingkung - Fitrisia, Yola; Natsir, MHD (Universitas Negeri Padang, 2024)
This study aims to identify the relationship between the intensity of gadget use and the social development of early childhood in Korong. With the increasing use of digital technology among children, it is important to understand its impact on their social skills. This study used a quantitative method with a survey design, involving 100 early childhood in Korong as a sample. Data were collected through a questionnaire that measured the frequency of gadget use and children's social skills including the ability to interact, share, and cooperate. Data analysis was carried out using the Pearson correlation technique to determine the strength and direction of the relationship between the two variables. The results showed a significant relationship between the intensity of gadget use and children's social development, with higher intensity of gadget use associated with lower social skills. These findings provide important insights for parents and educators regarding the need to regulate gadget use to support optimal social development in early childhood.